The impact of gadolinium on the reactor production of 153Sm - Uguru, E.H.; Sani, S.F. A.; Khandaker, Mayeen Uddin *; Rabir, M. H.; Moradi, F.; Ekpe, J. E.; Bradley, D.A. * (Elsevier, 2021)
Radioisotopes represent major sources of ionizing radiation, not least for use in medical applications, brachytherapy and nuclear medicine included. In this, the nuclear reactor is the main source of β- - γ emitting isotopes, an example product being 153Sm used in the treatment of pain arising from bone metastases. Present analysis relates to the potential of gadolinium neutron capture reaction, its impact on reactor production of radioisotopes and the proliferation resistant potential of thorium fuel cycle. A comparative analysis has been made of the impact of gadolinium on the production of 153Sm by UO2 and (Th, U) O2 fuels in a Westinghouse small modular reactor. Five fuel assemblies were investigated: one containing no gadolinium, the other four containing 16, 24, 34 or 44 gadolinium fuel rods. The code Monte Carlo N-Particle eXtended (MCNPX) integrated with the CINDER90 burn-up code was used for calculations. In the production of 153Sm the same trend is followed for the fuels containing gadolinium, increasing significantly with the number of gadolinium fuel rods. Zero production results from fuel assemblies without gadolinium. The concentration of 153Sm increases significantly with burn-up, indicating that gadolinium has a positive impact on the production of 153Sm.